Anticonvulsants From Nature - Kamboj, Pradeep; Singh, Ishpinder; Mahadevan, Nanjaian; Chaudhary, Gagandeep (Pharmacognosy Reviews)
Epilepsy is the second most common neurological disorder after stroke and shows a prevalence rate in 1-2% of the world population. Although several antiepileptic drugs are available, the treatment of epilepsy is still far from adequate. The current therapy of epilepsy with modern antiepileptic drugs is associated with side effects and drug interactions. Approximately 30% of the patients continue to have seizures with current drug therapy. Several plants used for the treatment of epilepsy in different systems of traditional medicine have shown antiepileptic activity in experimental animal models and many such plants claimed in the traditional system still remain to be scientifically investigated. In this review, we have compiled the reported herbal anticonvulsants with their research advancements.
Keywords: Anticonvulsant; Convulsions; Epilepsy; Gamma amino butyric acid; Maximal electroshock; Pentylenetetrazole